The Eurasian Dry Grassland Group (EDGG) in 2016–2017 - Venn, Stephen; Ambarli, Didem; Biurrun, Idoia; Dengler, Jürgen; Kuzemko, Anna; Török, Péter; Vhrahnakis, Michael (Hacquetia, 2018)
This report summarizes the activities and achievements of the Eurasian Dry Grassland Group (EDGG) from mid-2016 through to the end of 2017. During this period, the 13th Eurasian Grassland Conference took place in Sighişoara, Romania, and the 14th conference was held in Riga, Latvia. Te 10th EDGG Field Workshop on Biodiversity patterns across a precipitation gradient in the Central Apennine mountains was conducted in the Central Apennines, Italy, this time in addition to multi-scale sampling of vascular plants, bryophytes and lichens, also including one animal group (leaf hoppers). Apart from the quarterly issues of its own electronic journal (Bulletin of the Eurasian Dry Grassland Group), EDGG also fnalised fve grassland-related Special Features/Issues during the past 1.5 years in the following international journals: Applied Vegetation Science, Biodiversity and Conservation, Phytocoenologia, Tuexenia and Hacquetia. Beyond that, EDGG facilitated various national and supra-national vegetationplot databases of grasslands and established its own specialised database for standardised multi-scale plot data of Palaearctic grasslands (GrassPlot).